Genetic Regulation of Liver Metabolites and Transcripts Linking to Biochemical-Clinical Parameters - Ponsuksili, Siriluck; Trakooljul, Nares; Hadlich, Frieder; Methling, Karen; Lalk, Michael; Murani, Eduard; Wimmers, Klaus (Frontiers in Genetics, 2019)
Given the central metabolic role of the liver, its state is reflected by hepatic metabolites and transcripts. Biochemical-clinical plasma biomarkers, hepatic metabolites, transcripts and SNP genotypes of some 300 pigs were integrated by weighted correlation networks and genome-wide association analyses. Network-based approaches of transcriptomic and metabolomics data revealed linked of transcripts and metabolites of the pentose phosphate pathway (PPP). This finding was evidenced by using a NADP/NADPH assay and HDAC4 and G6PD transcript quantification with the latter coding for first limiting enzyme of this pathway and by RNAi knockdown experiments of HDAC4. Other transcripts including ARG2 and SLC22A7 showed link to amino acids and biomarkers. The amino acid metabolites were linked with transcripts of immune or acute phase response signaling, whereas the carbohydrate metabolites were highly enrich in cholesterol biosynthesis transcripts. Genome-wide association analyses revealed 180 metabolic quantitative trait loci (mQTL) (p < 10–4). Trans-4-hydroxy-L-proline (p = 6 x 10–9), being strongly correlated with plasma creatinine, showed strongest association with SNPs on chromosome 6 that had pleiotropic effects on PRODH2 expression as revealed by multivariate analysis. Consideration of shared marker association with biomarkers, metabolites and transcripts revealed 144 SNPs associated with 44 metabolites and 69 transcripts that are correlated with each other, representing 176 mQTL and eQTL. This is the first work to report genetic variants associated with liver metabolite and transcript levels as well as blood biochemical-clinical parameters in a healthy porcine model. The identified associations link between variation at the genome, transcriptome, and metabolome level with clinically relevant phenotypes. This approach has the potential to detect novel biomarkers displaying individual variation and promoting predictive biology in medicine and animal breeding.